Systematic-Constructive Theology: Formulating a Contextual Christology in the Era of Disruption - riris, duma (Hikmat : Jurnal Agama Kristen, 2025)
The era of disruption—marked by digitalization/AI and the ecologicalcrisis—demands a reconstruction of Christology that is both faithful toScripture and relevant to the practice of the Indonesian church. Thisstudy formulates a contextual Christology model based on systematicconstructivetheology by combining narrative-theological exegesis (theaxis of the Incarnation, Cross-Resurrection, Kingdom of God), traditionstudies (creeds, councils, Asian theology), and digital-liturgicalethnography in urban/suburban congregations (participantobservation, online liturgical/catechetical artifacts, and semistructuredinterviews). The analysis was conducted abductivelythrough three phases: descriptive (thick description), correlational(open-axial coding connecting findings with the loci of creation–sin–redemption–church–eschatology), and constructive (formulation oftheological propositions and derivation of operational principles). Theresult is a Christology–disruption–loci correlation matrix that ties“digital-incarnation,” “ecological-cross,” and “public-kingdom” into apraxis rubric: an incarnation-oriented hybrid liturgical design, a digitalcatechetical curriculum focused on student attention/affection, arhythm of digital asceticism (notification sabbath/fasting), antidisinformationliteracy, and ecological diaconia protocols (urbanfarming, green space restoration). The evaluation shows strong biblicalfidelity and systematic coherence, medium–strong contextualadequacy, and high practical applicability. This study presents aconfessio → constructio → conversio architecture that can be replicatedacross congregations, rejects the private-public dichotomy, and affirmsthe confession of “Jesus Christ is Lord” as the foundation of ecclesialtransformation in Indonesia’s digital-ecological space.